Effects of Sunn Hemp, Vermicompost, and Organic Fertilizers on Organic Strawberry Plant Growth, Yield, and Fruit Quality - Jianyu Li; Jeffrey K. Brecht; Shinsuke Agehara; Xin Zhao (International Journal of Fruit Science)
Nitrogen (N) supply and availability remains a major challenge in organic strawberry production under sandy soil conditions with low organic matter content and high nutrient leaching potential, calling for more systematic studies that address integrated nutrient management practices. In this study, summer cover crop sunn hemp (Crotalaria juncea L.), vermicompost, and organic fertilization programs including preplant application of granular organic fertilizer and in-season fertigation with liquid fish fertilizer were assessed for their impacts on plant growth, yield, and fruit quality of organically grown ‘Florida Brilliance’ strawberry (Fragaria ×ananassa Duch.). In the 2018–2019 season, sunn hemp showed positive trends for increasing early-season marketable fruit yield (p = .09) and whole-season total fruit number (p = .09) and yield (p = .08). In the 2019–2020 season, sunn hemp benefits for strawberry yield improvement were dependent on vermicompost application and organic fertilization. Vermicompost also exhibited potential to enhance early-season yields but requires optimization of application method and rate. The first season trial indicated liquid fish fertilizer as a more effective source of in-season N to enhance plant growth and fruit yield. In the second season, the combined program consisting of preplant fertilization and in-season fertigation increased early-season fruit numbers and yields, leading to the highest yielding potential for the whole season compared with the two in-season fertigation only treatments. However, the two in-season fertigation treatments starting with either higher or lower N rates resulted in similar levels of early- and whole-season fruit yields in general. The nutrient management practices did not show major effects on fruit soluble solids content, titratable acidity, and total anthocyanin content.